ECONOMICAL VIABILITY OF A LAMBS FINISHING SYSTEM IN THE CAMPAIGN REGION/RS - Piccoli, Milene; Corrêa, Gladis Ferreira; Rohenkohl, Júlio Eduardo; Tontini, Jalise Fabíola; Moreira, Sheilla Madruga; Rossato, Marivane Vestena (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708818 The study was conducted between March and June in a particular property of a member of the Association of Sheep Breeders of Dom Pedrito (ACODOPE). Sample consisted of 60 lambs, 50 animals and 10 Corriedale breed Texel, all barrows, milk tooth, with five to seven months old. Was sought throughout the experiment to assess the cost and profitability of a lambs finishing system. The animals were weighed throughout the experiment for the control of weight gain. To achieve the exact results of the production were evaluated and represented all the costs of implementation and operation of confinement as: Fixed Costs, Variable Costs and Cost of acquisition of animals. It was observed that the animals Texel lot remained less time to reach slaughter weight, therefore the cost of producing them was inferior to the other. Still had a loss of R 0.69 per kg bodyweight. Negative results were found in another two lots, the lot with Organic Phosphorus application associated with Vitamin B12 (FOB12) posted a loss of R 1.77 per kg bodyweight, and lot of animals without applying FOB12, R 0.75 per kg bodyweight. These results have made the termination system feedlot lambs, tested in this trial, uneconomical.